Answer:
n =7
Step-by-step explanation:
(n+1) +1 + (n-1) = value first row
3+ (2n-9) +n = value second row
The value has to be the same
Set the equations equal
(n+1) +1 + (n-1) =3+ (2n-9) +n
Combine like terms
2n+1 = 3n-6
Subtract 2n from each side
2n+1-1 -2n = 3n-6-2n
1 = n-6
Add 6 to each side
1+6 = n-6+6
7 = n
Answer:
Part A: Describe how you can decompose this shape into triangles: If you draw a line from each vertex to the vertex at the opposite side of the hexagon, you will form 6 triangles.
Part B: What would be the area of each triangle: 62.4
Part C: Using your answers above, determine the area of the table's surface: 374 .4
Step-by-step explanation:
Part A: Describe how you can decompose this shape into triangles: If you draw a line from each vertex to the vertex at the opposite side of the hexagon, you will form 6 triangles.
Part B: What would be the area of each triangle: bxh /2
12 x 10.4 /2
Part C: Using your answers above, determine the area of the table's surface: 374.4
You substitute M for 3 and C for 6. So you get E = (3)(6)(2) which equals 36.
2/x ^6-3 you do the opposite of everything